2001
DOI: 10.1002/1097-4660(200101)76:1<27::aid-jctb320>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the activity of papain in mixed reverse micellar systems in the presence of Tween80

Abstract: An enhancement in the activity of papain (EC 3.4.22.2) was described in mixed reverse micellar systems containing Tween80 compared with those without Tween80. By the use of these media, the hydrolytic and synthesis activities of papain were investigated in detail, respectively for the hydrolysis of N-a-benzoyl-L-arginine-p-nitroaniline (BNPNA) and the synthesis of the dipeptide ZGly-L-PheOMe (ZGPM). The reaction medium conditions (W 0 , pH and Tween80 concentration) were optimized for both the hydrolytic and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, the functional groups within the interior of these assemblies can be used to introduce selectivity. For example, reverse micelles bearing hydrophobic moieties on the outside and hydrophilic groups on the inside provide a scaffold that can readily bind to hydrophilic guest molecules in various biphasic systems. , Small molecule surfactants (e.g., sodium bis­(2-ethylhexyl)­sulfosuccinate (AOT)) or surfactant/phase transfer reagent mixtures based reverse micelles have been broadly explored for the purposes of protein purification, molecular sensing, biomolecular separations, heterogeneous catalysis, and as nanoreactors. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the functional groups within the interior of these assemblies can be used to introduce selectivity. For example, reverse micelles bearing hydrophobic moieties on the outside and hydrophilic groups on the inside provide a scaffold that can readily bind to hydrophilic guest molecules in various biphasic systems. , Small molecule surfactants (e.g., sodium bis­(2-ethylhexyl)­sulfosuccinate (AOT)) or surfactant/phase transfer reagent mixtures based reverse micelles have been broadly explored for the purposes of protein purification, molecular sensing, biomolecular separations, heterogeneous catalysis, and as nanoreactors. …”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that these components directly activate the enzyme by interacting with the enzyme and affecting the conformation of the enzyme (Goodman et al, 1967). When the amount of Tween 40 added is a certain value, it will achieve the best emulsifying effect, so that the enzyme and the substrate can be fully contacted (Wyss et al, 2001;Fan et al, 2015). However, the rate of enzymatic hydrolysis does not continue to increase after the amount of Tween added exceeds its optimal amount.…”
Section: Effect Of Tween 40 Addition On Enzymatic Hydrolysis Of Bcaromentioning
confidence: 99%
“…With the synthetic substrate, the inhibition was due to a competition between the substrate and the inhibitor molecules for the enzyme (50). Papain is denatured by SLS (51) but its activity can be enhanced with moderate amounts of Tween 80 (52). Analysis of kinetic data showed that SLS acts as a partial non-competitive inhibitor for bromelain, and demonstrated that bromelain is resistant to SLS binding and denaturation (53).…”
Section: Interaction Enzymes-surfactantsmentioning
confidence: 99%